Application of probability-based multi–objective optimization in material engineering - Zheng, Maosheng (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: Althought many methods have been proposed to deal with the problem of  material selection, there are inherent defects of additive algorithms and subjective factors in such methods. Recently, a probability-based multi–objective optimization was developed to solve the inherent shortcomings of the previous methods, which introduces a novel concept of preferable probability to reflect the preference degree of the candidate in the optimization. In this paper, the new method is utilized to conduct an optimal scheme of the switching material of the RF-MEMS shunt capacitive switch, the sintering parameters of natural hydroxyapatite and the optimal design of the connecting claw jig.Methods: All performance utility indicators of candidate materials are divided into two groups, i.e., beneficial or unbeneficial types for the selection process; each performance utility indicator contributes quantitatively to a partial preferable probability and the product of all partial preferable probabilities makes the total preferable probability of a candidate, which transfers a multi–objective optimization problem into a single–objective optimization one and represents a uniquely decisive index in the competitive selection process.Results: Cu is the appropriate material in the material selection for RF - MEMS shunt capacitive switches; the optimal sintering parameters of natural hydroxyapatite are at 1100°C and 0 compaction pressure; and the optimal scheme is scheme No 1 for the optimal design of a connecting claw jig.Conclusion: The probability-based multi-objective optimization can be easily used to deal with an optimal problem objectively in material engineering.
Keywords: multi-objective optimization; probability theory; preferable probability; material engineering; scheme selection